WorldFish-developed Generation 3 rohu grows more than 30% faster than conventional rohu strains - Yeasin, Mohammed; Ali, Md. Rayhan; Fakhruddin, Md.; Hamilton, Matthew (WorldFish, 2022)
In 2020 and 2021, WorldFish released the genetically-improved ‘Generation 3’ or ‘G3’ rohu strain as hatchlings to several hatcheries on a limited scale. The hatcheries have subsequently grown these fish to adulthood and have begun producing seeds for sale to nurseries and farmers. In parallel to the release of G3 rohu hatchlings to hatcheries, WorldFish conducted an on-farm performance trial involving 19 semi-commercial farms in Jashore, Natore, and Rajshahi districts from May 2021to June 2022.This brochure briefly demonstrates the growth performance of G3 rohu compared to an unimproved strain.